(3QSGdI GdJfRjgs - (3MeRI Hf Ydj Hf CMeO GdaGQSj GdMGcej GdOQRj,J (B433 (3g` s
(3ChdgG (B:s
(3dcfi CPcQ ai gPG GdcJGH Ydi GNJUGQ GdObGFb heMV GdJhMjO hGdMbGFb s
(3BNQgG (B:s
(3hGdMeO hGdTcQ dg hMOg hgh MSHfG JeJ s
(3Vef eLehY , JQJjHgG (B: 3s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B656s
Keywords: (3GdJhMjO hGdedd hGdfMds